Psychological well-being: A study of physical education students - Yahya Eko Nopiyanto; Septian Raibowo; Andika Prabowo; Ibrahim Ibrahim (Universitas Sriwijaya, 2022)
Knowing the level of psychological well-being of physical education students is the main objective of this study. A total of 25 students were sampled to collect the data needed in this study. Data collection techniques and instruments used a questionnaire consisting of 20 statement items and 6 indicators, namely: self-acceptance, relationships, goals, independence, adaptation, and self-potential. The data that has been collected was analyzed using the mean value and standard deviation to produce 5 categories. The results of the research on each indicator show that: 1) the physical education student self-acceptance indicator has a mean score of 14.96 and a standard deviation of 2.75; 2) the physical education student relation indicator has a mean score of 16.32 and a standard deviation of 2.43; 3) the indicators of physical education students' goals have a mean score of 12.72 and a standard deviation of 2.42; 4) on the independent indicators of physical education students have a mean score of 10.80 and a standard deviation of 1.95; 5) on the indicators of adaptation, physical education students have a mean score of 12.56 and a standard deviation of 2.10; 6) on the indicators of self-potential physical education students have a mean score of 12.20 and a standard deviation of 2.10. The conclusion of the study states that the psychological well-being of physical education students is in the high category.